SARS-COV-2 pandemic as a factor in the social exclusion of the elderly - Wieczorkowska, Magdalena; Przyłęcki, Paweł; Pawlak-Kałuzińska, Agnieszka (Research on social problems in (pre-)pandemic reality, 2023)
Older adults are the group vulnerable to various form of exclusion including – among others - the workplace, in the healthcare system, the insurance system, in culture or in digital world. Inclusive actions which – due to the demographic trends - are undertaken globally, have been limited due to SARS-CoV-2 pandemic. The coronavirus has touched – directly or non-directly – every single person, forcing them to modify, to stop or to undertake new activities. In many areas its consequences are negative - the pandemic deepened the existing inequalities in such areas as: medical (difficulty in treating conditions other than COVID-19, increasing crisis in the health care system), socio-cultural (limitation of social contacts and in the use of cultural goods and services), economic (job losses and increasing unemployment, bankruptcy of companies, financial state interventions), religious and spiritual (isolation, difficulty in participation in religious ceremonies), political (deepening of socio-political divides du to restrictions, changes in national and international arrangements of political powers). The pandemic increased social isolation of older adults, which they had very often previously experienced. From the beginning, media broadcast underlined that older adults are particular group of people, that should be protected. Thus, many restrictions and recommendation have been implemented, which eventually has led to loneliness. In the paper we present selected results of the study on psychosocial and health consequences of isolation caused by the SARS-CoV-2 pandemic among persons aged 55+. The data will show, how the pandemic has changed the situation of respondents in the area of social activity and social contacts being – to some extent – a factor of social exclusion.